Innovative capacity and the performance of businesses incubated in university incubator units: Empirical study from universities in Thailand - Theeradej Rakthai; Somnuk Aujirapongpan; Kwanrat Suanpong (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
The purpose of this research is to study the factors related to the performance of the entrepreneurs who passed through the stages of business development at the university business incubators in Thailand. These factors consist of various characteristics, namely, leadership orientation, entrepreneurial orientation, network capacity, and innovative capacity. The sample group consisted of 220 businesses that had passed through a university business incubator in Thailand. The SPSS Statistics program calculated the basic statistics, as well as the relationship test for each factor studied, and examined the statistics using a structural equation model (SEM). The results revealed that the characteristics of leadership orientation, entrepreneurial orientation, network capacity, innovative capacity, and entrepreneurial performance had relationships in the same direction. Furthermore, an analysis of the relationships between the factors found that entrepreneurial orientation had positive relationships with network capacity and innovative capacity, leadership orientation had positive relationships with innovative capacity and entrepreneurial performance, and innovative capacity had a positive relationship with entrepreneurial performance. These relationships summarize a developmental model for the innovative capacity and performance of businesses that have passed through the university business incubators in Thailand.
Keywords: 650; entrepreneurial orientation; innovative capacity; business performance; university business incubator; open innovation